2017
DOI: 10.1080/21623945.2017.1372871
|View full text |Cite
|
Sign up to set email alerts
|

Fifty shades of white: Understanding heterogeneity in white adipose stem cells

Abstract: The excessive expansion of white adipose tissue underlies the global obesity epidemic. However, not all fat is equal, and the impact of heterogeneity on the development and expansion of different adipose depots is becoming increasingly apparent. Two mechanisms are responsible for the growth of adipose tissue: hyperplasia (increasing adipocyte number) and hypertrophy (increasing adipocyte size). The former relies on the differentiation of adipocyte stem cells, which reside within the adipose stromal vascular fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 81 publications
0
36
0
Order By: Relevance
“…These cells respond to surplus energy through processes of proliferation or expansion so called adipocyte hyperplasia or adipocyte hypertrophy, respectively. Preadipocytes of subcutaneous adipose tissue replicate and differentiate into mature adipocytes (adipocyte hyperplasia) more efficiently than those of visceral depot [25]. The mature adipocyte has its maximum capacity for expansion which is determined by genetic, gender or certain hormones [25][26][27].…”
Section: Subcutaneous Fatmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells respond to surplus energy through processes of proliferation or expansion so called adipocyte hyperplasia or adipocyte hypertrophy, respectively. Preadipocytes of subcutaneous adipose tissue replicate and differentiate into mature adipocytes (adipocyte hyperplasia) more efficiently than those of visceral depot [25]. The mature adipocyte has its maximum capacity for expansion which is determined by genetic, gender or certain hormones [25][26][27].…”
Section: Subcutaneous Fatmentioning
confidence: 99%
“…Preadipocytes of subcutaneous adipose tissue replicate and differentiate into mature adipocytes (adipocyte hyperplasia) more efficiently than those of visceral depot [25]. The mature adipocyte has its maximum capacity for expansion which is determined by genetic, gender or certain hormones [25][26][27]. The study by Sato et al [28] in non-diabetic Japanese adults indicates that the maximum storage capacity of abdominal subcutaneous fat occurs at BMI of 23-24 kg/m 2 in women and 24-25 kg/m 2 in men.…”
Section: Subcutaneous Fatmentioning
confidence: 99%
“…Previous research has shown that there exists a good deal of heterogeneity between ASCs derived from different individuals and even from different regions within the same individual. 31,32 Overall though, these results indicate that the FPTM does not have a negative effect on ASC gene expression and cell behavior in vitro.…”
Section: Response Of Ascs To Fptm In Vitromentioning
confidence: 71%
“…However, while all WAT depots are absent in seipin-deficient CGL patients, including those spared in AGPAT2 deficiency, seipin appears dispensable for BAT development, at least in mice 7,30,31 . Thus, it is increasingly apparent that the pathways governing the development and expansion of adipose mass differs significantly between depots depending on location and the identity of the stem cells involved 32,33 . Such complexity is also likely to apply when considering the roles of different GPAT isoforms in these processes.…”
Section: Discussionmentioning
confidence: 99%